2017
DOI: 10.1002/dev.21543
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal respiratory sinus arrhythmia and behavioral engagement on mother‐child physiological coregulation

Abstract: THE EFFECTS OF MATERNAL RESPIRATORY SINUS ARRHYTHMIA AND BEHAVIORAL ENGAGEMENT ON MOTHER-CHILD PHYSIOLOGICAL COREGULATIONParent-child coregulation, observed as the active organization and coordination of parents' and children's behavioral and physiological states, is an important precursor for children's developing self-regulation, but we know little about how individual parent factors shape parent-child coregulation. We examined whether differences in maternal physiology and behavioral engagement were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…Positive RSA synchrony between 4-to 6-month-old infants and their mothers was associated with co-regulation during a still-face paradigm (Abney, da Silva, & Bertenthal, under reviewb). Furthermore, three-year-old children and their mothers showed stronger RSA synchrony during higher levels of maternal teaching and weaker synchrony when mothers were disengaged (Skoranski, Lunkenheimer, & Lucas-Thompson, 2017). On the other hand, negative RSA synchrony in a video watching situation was related to higher child-reported empathy at ages 9-14 years, while positive RSA synchrony was associated with lower levels of empathy among the dyads (Creavy, Gatzke-Kopp, Zhang, Fishbein, & Kiser, 2020).…”
Section: Physiological Synchronymentioning
confidence: 88%
“…Positive RSA synchrony between 4-to 6-month-old infants and their mothers was associated with co-regulation during a still-face paradigm (Abney, da Silva, & Bertenthal, under reviewb). Furthermore, three-year-old children and their mothers showed stronger RSA synchrony during higher levels of maternal teaching and weaker synchrony when mothers were disengaged (Skoranski, Lunkenheimer, & Lucas-Thompson, 2017). On the other hand, negative RSA synchrony in a video watching situation was related to higher child-reported empathy at ages 9-14 years, while positive RSA synchrony was associated with lower levels of empathy among the dyads (Creavy, Gatzke-Kopp, Zhang, Fishbein, & Kiser, 2020).…”
Section: Physiological Synchronymentioning
confidence: 88%
“…Further, we did not control for individual differences in breathing rate nor for physical touch between parent and child, which could influence RSA. If PNS functioning underlies parents’ abilities to engage with children, it will be important to pursue more specific and comprehensive measurement of parental PNS and SNS functioning in studying how it is involved in physiological coregulation (Skoranski, Lunkenheimer, & Lucas-Thompson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, Helm et al (2018) found that parasympathetic synchrony disappears in dyads with 3–4-year-olds after de-trending, suggesting different analytic techniques lead to different conclusions. Regardless, several studies that use strong multilevel modeling strategies demonstrate that parasympathetic synchrony in toddlerhood is associated with lower maternal and child psychopathological symptoms (Gray et al, 2018; Lunkenheimer et al, 2015 & 2018b, same sample), increased maternal teaching and engagement (Skoranski et al, 2017; same sample as Lunkenheimer et al, 2015; 2018b), and a lack of a history of maltreatment (Creaven et al, 2014). Shih et al (2019) found that parent parasympathetic activity during a frustrating puzzle task positively predicted child parasympathetic activity during recovery, but did not test for associations with behavior or child functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Research on caregiver–child physiological synchrony has been growing rapidly in recent years, as it is suspected to help explain how caregivers and children interact with and respond to each other, thus affecting children's long-term development. Physiological synchrony has been measured and discussed using various terms (e.g., concordance, attunement, coregulation, coordination) with little consistency or clarity in the construct's exact definition (e.g., Saxbe et al, 2014; Skoranski, Lunkenheimer, & Lucas-Thompson, 2017; Suveg et al, 2019). Generally, the concept is used to refer to the association between some measure of physiological activity in the caregiver and that same measure in the child in response to a task or in a particular context.…”
Section: Introductionmentioning
confidence: 99%